Impersonations: TROUBLING THE PERSON IN LAW AND CULTURE - SHERYL N. HAMILTON (University of Toronto Press, 2013)
On 25 February 1990, Theresa Marie Schiavo, subsequently known to the world as ‘Terri’ Schiavo, suffers a cardiac arrest apparently caused by a potassium imbalance. Her brain is deprived of oxygen for more than five minutes and severe brain damage results. Her husband, Michael, is appointed her guardian and various medical efforts are undertaken to rehabilitate her. Terri cannot speak or care for herself; she is fed through a feeding tube surgically implanted into her abdomen as she would aspirate any food or liquids placed in her mouth. Within three years of her cardiac arrest, she is pronounced by doctors to be in a ‘persistent vegetative state’ (PVS), a medical term to denote a lack of self-awareness, language comprehension, expression, and interactivity. These attributes exist despite periods where patients’ eyes may be open, they exhibit some reflexes, and can even make some noises, words, and faces. In addition to finding Terri in a state of PVS, doctors note that she has no hope of recovery After a 1992 medical malpractice suit results in an out-of-court settlement, including damages of $300,000 for Michael Schiavo and approximately $750,000 to be held in trust for Terri’s care, Michael and Terri’s parents, Robert and Mary Schindler, have a falling out regarding the preferred course of her therapeutic treatment. Terri’s parents attempt to have Michael removed as her guardian in 1993, but the court refuses; further, a court-appointed guardian reports in 1994 that Michael has acted appropriately throughout. In 1998, Michael petitions a Florida court to have his wife’s feeding tube removed, claiming that while she did not leave a ‘living will,’ she indicated to him verbally that she would not want to continue living in such a state. A second court-appointed guardian confirms that Terri is in a PVS, but also notes that Michael’s decision-making may be influenced by his conflict of interest, as he stands to inherit her estate upon her death. Judge George Greer of the Pinellas-Pasco County Circuit Court finds Michael’s testimony as to Terri’s wishes credible and orders the removal of the feeding tube on 11 February 2000. Her death will result in approximately seven to fourteen days.2 Her parents appeal that decision immediately, asserting that Terri is responsive and can recover with treatment. What follows is five further years of bitter legal wrangling over the status of Terri Schiavo and what should happen to her.